2012
DOI: 10.1007/s00701-012-1309-1
|View full text |Cite
|
Sign up to set email alerts
|

Uncovertebral hypertrophy is a significant risk factor for the occurrence of heterotopic ossification after cervical disc replacement: survivorship analysis of Bryan disc for single-level cervical arthroplasty

Abstract: These findings suggest that the condition of the uncovertebral joint must be evaluated in preoperative planning for Bryan cervical arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…29 In other studies, patients were classifi ed into a "ROM-preserving HO" group and a "ROM-affecting HO" group, according to whether the ROM was affected. 30 Both classifi cations were applied in this meta-analysis, and the results indicated that different grades of HO have distinct infl uences on clinical outcomes, making it inappropriate to simply classify patients into HO and Copyright © 2015 Wolters Kluwer Health, Inc. Unauthorized reproduction of this article is prohibited.…”
Section: Discussionmentioning
confidence: 99%
“…29 In other studies, patients were classifi ed into a "ROM-preserving HO" group and a "ROM-affecting HO" group, according to whether the ROM was affected. 30 Both classifi cations were applied in this meta-analysis, and the results indicated that different grades of HO have distinct infl uences on clinical outcomes, making it inappropriate to simply classify patients into HO and Copyright © 2015 Wolters Kluwer Health, Inc. Unauthorized reproduction of this article is prohibited.…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, levels of surgery, indications for surgery, and the carpentry of arthroplasty were the reported factors that could affect the formation of HO after cervical arthroplasty. 6,18,24,35,36,42,44 In the literature, short to midterm clinical outcomes of cervical arthroplasty were not significantly impaired by HO. 34,[40][41][42] There was also heterogeneity in both location and morphology of HO formation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest risk factors, including advanced age, male sex, surgical techniques, preexisting uncovertebral joint hypertrophy, surgical indications, types of prosthesis, multilevel disease, and postoperative biomechanical changes. 7,[27][28][29][34][35][36]39,40 CDA, rather than ACDF as the standard of care, aims to restore joint function. Theoretically, if the artificial disc can completely function with its physiological motion at the indexed level, the likelihood of HO formation will be low.…”
Section: Discussionmentioning
confidence: 99%